Review on diabetes mellitus - P, Vyshnavi; P, Narayana swamy; P, Venkatesh (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2022)
Diabetes is one of the most common chronic disease, which occurs when the pancreas does not produce enough insulin, or when the body cannot effectively use the insulin it produces. This leads to an increased concentration of glucose in the blood (hyperglycemia) Diabetes mellitus (DM) also known as simply diabetes, is a group of metabolic diseases in which there are high blood sugar levels over a prolonged period This high blood sugar produces the symptoms of frequent urination, increased thirst, and increased hunger. Untreated, diabetes can cause many complications. Acute complications include diabetic ketoacidosis and non-kenotic hyperosmolar coma. Serious long-term complications include heart disease, stroke, kidney failure, foot ulcers and damage to the eyes. Diabetes is due to either the pancreas not producing enough insulin, or the cells of the body not responding properly to the insulin produced Type 1 diabetes is a chronic autoimmune disease characterized by insulin deficiency and resultant hyperglycemia. Knowledge of type 1 diabetes has rapidly increased resulting in a broad understanding about many aspects of the disease, including its genetics, epidemiology, immune and β-cell phenotypes, and diseased burden. Interventions to preserve β cells have been tested, type 1 diabetes and our ability to standardize clinical care and decrease disease-associated complications and burden. The presence of additional chronic conditions has a significant impact on the treatment and management of type 2 diabetes (T2DM). Little is known about the patterns of comorbidities in this population. The aims of this study are to quantify comorbidity.